Aplikasi Penjualan Online Pada Pempek Flamboyant Berbasis Web - Qorria Hilallia; Afriyudi Afriyudi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
In the current era of globalization, where everything is required to be fast-paced, so time is a very valuable thing. Using time properly and correctly will certainly improve business performance, therefore management is needed that can help minimize inefficient use of time. The flamboyant pempek shop has not used a computer application that can assist in sales transactions. The customers of the flamboyant pempek shop are residents around the city of palembang, with the development of technology, palembang pempek as a special food, began to be attracted by many people outside the city of Palembang. So the researchers took the initiative to develop a mobile-based system at the flamboyant pempek shop. The methodology used to design this system is Extreme Programming. The use of the up-selling method in programming is used to increase and facilitate sales of the flamboyant pempek shop. The final result of this research is a web-based application